Export Quality in Advanced and Developing Economies : Evidence from a New Data Set - Henn, Christian; Papageorgiou, Chris; Romero, Jose Manuel; Spatafora, Nikola (World Bank, Washington, DC, 2017)
This paper develops new estimates of export quality, based on bilateral data, which are far more extensive than previous efforts. The data cover 166 countries and hundreds of products over 1962-2014. The analysis finds that quality upgrading is particularly rapid during the early stages of development. There is significant cross-country heterogeneity in the growth rate of quality. Within any given product line, quality converges over time to the world frontier. Institutional quality, liberal trade policies, foreign direct investment inflows, and human capital all promote quality upgrading, although their impacts vary across sectors. The results suggest that reducing barriers to entry into new sectors can allow economies to benefit from rapid quality convergence over time.